Prevalence of white spot lesions in children up to 71 months of age in Gujarat state - Priyanka R Kashyap; Manpreet Kaur; Ganesh Mahadevan (Wolters Kluwer Medknow Publications, 2023)
Introduction: The earliest sign of a new carious lesion is the appearance of chalky white spots on the surface of the tooth, indicating an area of demineralization of enamel. At this stage, the demineralization process can be reversed or arrested. This study aimed to determine the prevalence of white spot lesions (WSLs) among children up to 71 months in Gujarat state and to increase awareness among parents about its various preventive measures. Materials and Methods: Oral examination was done using the mouth mirror and tongue depressor. The prevalence of WSL was recorded using the International Caries Detection and Assessment System II coding and WSL index by Gorelick. Results: The overall prevalence of WSL was 31.8% (n = 2025) in Gujarat state. The parents of the participating children explained the various preventive measures to prevent decay followed by diet counseling and toothbrushing techniques. Conclusion: Knowledge of the actual prevalence of WSL will help in the implementation of appropriate and timely preventive measures required to decrease the incidence of early childhood caries in that region.